2020
DOI: 10.1111/1759-7714.13282
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection maybe not associated with primary lung cancer in the Fujian population of China

Abstract: Background To investigate whether human papillomavirus (HPV) infection is associated with primary lung cancer among the Fujian population. Methods HPV infection was detected in 140 pairs of lung cancer tissues and matched paracancerous tissues by examining the 21 clinically relevant HPV types using a combination of viral highly conserved L1 region PCR amplification and specific probe reverse hybridization. Paired χ2 test was used to analyze differences in detection rates of HPV between lung cancer and paracanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This result was consistent with the literature data, in particular in a 2020 study that included 140 patients with primary lung cancer, where it was shown that the total infection rate of the sample included in the study was 20.7%. The virus was detected in 9.3% of the tumor samples (13 out of 140) and in 16 paired samples of normal and tumor tissues (11.4%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was consistent with the literature data, in particular in a 2020 study that included 140 patients with primary lung cancer, where it was shown that the total infection rate of the sample included in the study was 20.7%. The virus was detected in 9.3% of the tumor samples (13 out of 140) and in 16 paired samples of normal and tumor tissues (11.4%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the leader in the frequency of occurrence was HPV genotype 18 (36.8%), which was consistent with the world literature data on the definition of HRC HPV among the oncopathologies of various localizations [ 19 , 20 ]. In a sample of 140 patients with primary lung cancer, it was shown that in 16 paired samples of normal and tumor tissues, 7 cases of HPV type 16 were detected, 4 with HPV type 18, 3 with HPV type 42, 1 with the HPV 6 genotype, and 1 sample with a mixed infection with HPV 18 and 33 genotypes [ 15 ]. In another study, it was shown that in the study of 102 samples of lung tumor tissues and 48 control samples, the presence of HPV DNA was determined in 52.9% (54/102) of cases and in 25% of cases (12/48), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that the human papillomavirus (HPV) infection could be associated with LCW, since DNA from HPV16, 18, 30, 31, 33, and 39 were detected in women LC tissues (44)(45)(46); however, recent studies rule out this association, since there is no evidence of DNA from HPV in lung tumors, and no differences were found between the presence of HVP in lung tumors and controls (47)(48)(49).…”
Section: Lcw Etiological Factorsmentioning
confidence: 99%
“…As we all know, lung cancer is one of the common tumors that seriously threaten human health nowadays. [42] Although there are more and more treatment methods for tumors in clinical practice, the treatment options for different pathological types of tumors are very different. According to the pathology, genetic alteration, tumor stage and patient's condition, the treatment for NSCLC mainly includes surgery, radiotherapy, chemotherapy, immunotherapy, molecular targeted therapy, combined therapy and other modalities.…”
Section: Discussionmentioning
confidence: 99%